1990
DOI: 10.1080/00288233.1990.10428468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co, Cu, Fe, Mn, Mo, Se, and Zn supplementation on the elemental content of soft tissues and bone in sheep grazing ryegrass/white clover pasture

Abstract: , and Mn (l05-455) on the concentrations of major and minor elements in some organs, soft tissues, and bones of 72 Romney wethers were measured. The treatment and two control groups were each made up of six sheep. Trace elements were administered daily for 84 days and the sheep grazed as one group on ryegrass/white clover pasture. The animals were then shorn and slaughtered, and some organs, tissue, and bones removed for elemental analyses. A 40% increase in liver Cu occurred when Cu intakes were increased. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 35 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…in sheep it was observed that a two-to three-fold increase in the ca, P, Mg, Na, K, cu, Mn, Fe and Zn intakes had no effect on their muscle and bone mineral concentrations. However, increased cu, Mn and Fe intakes did increase liver cu, digestive tract, bone and spleen Mn, and digestive tract Fe concentrations, respectively in sheep (Grace & Lee 1980. Thus it is most likely that in deer, the mineral content associated with liveweight gain, largely muscle and bone, is not influenced by varying mineral intakes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…in sheep it was observed that a two-to three-fold increase in the ca, P, Mg, Na, K, cu, Mn, Fe and Zn intakes had no effect on their muscle and bone mineral concentrations. However, increased cu, Mn and Fe intakes did increase liver cu, digestive tract, bone and spleen Mn, and digestive tract Fe concentrations, respectively in sheep (Grace & Lee 1980. Thus it is most likely that in deer, the mineral content associated with liveweight gain, largely muscle and bone, is not influenced by varying mineral intakes.…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, supplementation of deer, cattle and sheep with cu leads to a marked increase in liver cu concentrations (Grace et al 2004). it was found in sheep that there was little or no change in the cu concentrations of tissues other than liver following cu supplementation (Grace & Lee 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minerals were determined in a single analysis by inductively coupled argon plasma atomic emission spectrometry [Lee, 1983;Grace and Lee, 1990]. …”
Section: Chemical Analysismentioning
confidence: 99%
“…Calcium, phosphorus, potassium, sodium, sulphur, iron, magnesium, zinc, copper, manganese, and selenium were determined in the lipid extracted samples in single analysis by inductively coupled argon plasma atomic emission spectrometry (Lee 1983;Grace & Lee 1990).…”
Section: Chemical Analysismentioning
confidence: 99%